Social Innovation in a University: Accelerator Programs of a Center for Social Entrepreneurship in the Philippine Setting - Melanie Ramiro Banzuela; Lauro Cipriano Silapan; Jr., Jovenal M Arnaiz (Soegijapranata Catholic University, 2024)
The paper traces the managerial plans and decisions made towards the development of the Center for Social Entrepreneurship of the University of San Carlos in Cebu City, Philippines under the auspices of the School of Business and Economics and Santa Clara University's Miller Center for Social Entrepreneurship in California. Using the action research approach, the Center and its two Accelerator Programs namely the Global Social Benefit Institute Boost and Online Accelerator Programs were studied. Participants for the first cohorts were called Potential Social Enterprises (PSEs) and Mature Social Enterprise (MSEs) for the Boost and Online Accelerator Programs, respectively. A total 27 PSEs and 5 MSEs joined the first cohort. Few scholars have studied accelerators that support social enterprises. In contrast to incubators, accelerators expose social entrepreneurs to market forces and provide the intense process of mentoring, education, and expansion of networks which have a lasting impact on participants. Overall, both Boost and Online Accelerator Programs proved effective in developing the competencies of the social enterprises. The results presented in this paper covers the period of implementation from the time the center was launched in February 2018 to February 2019. This study will cover the progress towards the center's goals, verifiable indicators, activities conducted, survey results, key insights and initial recommendations moving forward. The findings of the study support similar findings of other authors that accelerators for social enterprises play an important role in developing social ventures. Accelerators can contribute to the development of new ventures at several stages.